Penurunan Waste Proses Produksi Produk RJK di Departemen DEW PT. X dengan Value Stream Mapping - Franky Saputra; I Gede Agus Widyadana (Jurnal Titra, 2013)
PT. X wants to increase profit that obtained from RJK product. Increasing the price can make RJK product will lose with its competing product. PT. X chooses to eliminate wastes that exist in production so higher profit can be obtained. PT. X wants to eliminate non value added activity that exists in RJK production process. Identification waste is done by the help of value stream mapping. Some wastes are located on Main line, CR line, and BYM line. Those wastes happen because of a lot of breakdown on combine line, over bulking, and BYM line does not have independent line because BYM line does not have a cutter. Combine line’s breakdown mainly caused by too long blend changeover or BCO time. Some improvements are done to eliminate waste on Main line, CR line, and BYM line. SMED concept is applied to speed up the BCO time so breakdown time of combine line will reduce. Alarm or visual alert installation is done so overbulking does not happen again. Searching for cutter at other affiliate is done so BYM line has independent line. Those improvements give impact by reducing NVA about 2.44 % at Main line, 0.48 % at CR line, and 1.4 % at BYM line.